“Stop Waking the Dead”: Internet Child Sexual Abuse and Perspectives on Its Disclosure - Katz, Carmit (Journal of interpersonal violence, 2021)
The phenomenon of Internet child sexual abuse (ICSA) has been receiving growing attention over the last decade, and studies have promoted knowledge with respect to the phenomenon’s epidemiology, as well as to characteristics of the victims, perpetrators, and dynamics in these cases. The current retrospective study sought to delve into the disclosure component in cases of ICSA. The sample comprised 52 cases of adolescents who arrived at a child advocacy center (CAC) following ICSA. Analysis of these cases was targeted to capture the multifaceted nature of disclosure using those perspectives that could be documented by the CAC staff—of the practitioners, the adolescents, and their parents. Beyond the descriptive results regarding the victims and the nature of the abuse, the case analyses illustrate the disclosure process as experienced by the various parties involved, highlighting the challenging nature of this aspect of the phenomenon. For the parents, the disclosure experience can perhaps be best epitomized by the expression that was heard repeatedly—“Stop waking the dead”—an expression that indicated their wish to bring the subject to a close. The difficulty in disclosing such incidents was also illustrated by the fact that 20 children in the current sample were reluctant to collaborate during the CAC process. In fact, according to these data, most of the incidents were revealed following a police investigation rather than by a disclosure initiated by the children themselves. Focusing on this specific aspect of ICSA—that is, disclosure—enables a new perspective on it and stresses the need to further study it in such cases. A better understanding of the disclosure experience as it pertains to the individuals involved in cases of ICSA may improve and help modify future prevention and intervention efforts in the field.